Analyzing the Crimea Bridge Explosion in The Guardian and CNN Online News: Critical Linguistics - Ulya, Ika Ni'matin (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This research focuses on analyzing the types of grammar and ideological representations in the news texts of The Guardian and CNN online news using the Critical Linguistics analysis model of Roger Fowler et.al (1979). Then the Discourse Historical Approach from Ruth Wodak (2001) is used to know the historical background of this topic. This research uses a descriptive qualitative method to find out what types of grammar are contained in the news text and how the grammar represents the ideology of the news. The explosion occurred as a result of the conflict between Russia and Ukraine. This topic has attracted public attention, therefore, online news media such as The Guardian and CNN are discussing it. At this time online news media plays an important role in disseminating information, but in fact the language used in online news media can contain certain ideologies that benefit one group and harm other groups. Based on the results of Critical Linguistics analysis from Roger Fowler et.al (1979), it is found that the ideology of the two online media is anti-Russian and pro-Ukrainian. The findings of this study show that there are 28 types of grammar in The Guardian and 17 grammatical strategies in CNN. The type of grammar that often appears from both media is transitivity grammar. In representing their ideology, both online media often use negative lexical choices to give negative references to the Russian side. Future researchers can develop their analysis by using different theoretical studies and objects.